Mechanisms of Macrophage Immunomodulatory Activity Induced by a New Polysaccharide Isolated From Polyporus umbellatus (Pers.) Fries - Liu, Chun-Ping; Li, Xiong; Lai, Ge-Na; Li, Jin-Hua; Jia, Wen-Yu; Cao, Ying-Ying; Xu, Wen-Xing; Tan, Qing-Long; Zhou, Chang-Yuan; Luo, Min; Zhang, Xue-Ying; Yuan, Dao-Qing; et al. (Frontiers in Chemistry, 2020)
Bladder cancer is one of the most malignant tumors closely associated with macrophage immune dysfunction. The Chinese medicine polyporus has shown excellent efficacy in treating bladder cancer, with minimal side effects. However, its material basis and mechanism of action remain unclear. A new water-soluble polysaccharide (HPP) with strong immunomodulatory activity was isolated from the fungus Polyporus umbellatus (Pers.) Fries. HPP had an average molecular weight of 6.88 kDa and was composed mainly of an -(1→4)-linked D-galactan backbone. The immunomodulatory activity of HPP was determined in vitro, and the results revealed that it could obviously increase the secretion of immune factors by IFN-γ-stimulated macrophages, including nitric oxide (NO), interleukin-6 (IL-6), interleukin-1β (IL-1β), RANTES and interleukin-23 (IL-23), and the expression of the cell membrane molecule CD80. In addition, HPP was recognized by Toll-like receptor 2 (TLR2) and activated the signaling pathways of NF-κB and NLRP3 in a bladder cancer microenvironment model, indicating that HPP could enhance host immune system function. These findings demonstrated that HPP may be a potential immune modulator in the treatment of immunological diseases or bladder cancer therapy.